Pengelolaan Program Pendidikan di Masa Pandemi - Adin Suryadin (STAI Terpadu Yogyakarta, 2022)
The purpose of this study was to find out how the educational management of the Yaumi Fatimah Integrated Islamic Elementary School managed the learning process during the pandemic starting from preparation, implementation, monitoring, and evaluation. Where during this pandemic all the learning system processes changed from face-to-face meetings in the classroom to online or online learning. In this study using the observation method and the interview method, where in the observation method the researcher monitors almost every day for two months how the online learning process is at school, while the interview method is conducting interviews with school principals and ustadz-ustadz how the online learning process is. The aspects that were observed and interviewed were aspects of preparation, aspects of implementation, aspects of monitoring, and aspects of evaluation. The population of this study was the principal and ustadz-ustadzah at the Yaumi Fatimah Kudus Elementary School, all of which amounted to 8 ustadz-ustadzah. The results of research at the Yaumi Fatimah Kudus Integrated Islamic Elementary School with online learning the average value is only 6.2 (below the KKM), while the average score at face-to-face meetings can reach 8.0 this value is above the KKM target (completeness criteria). minimum) the KKM is 7.5.